2019
DOI: 10.1186/s11671-019-3050-7
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Gamut and Polarization-Independent Structural Color at Optical Sub-diffraction-Limit Spatial Resolution Based on Uncoupled LSPPs

Abstract: The decreasing pixel size of digital image sensors for high-resolution imaging brings a great challenge for the matching color filters. Currently, the conventional dye color filters with pixel size of several microns set a fundamental limit for the imaging resolution. Here, we put forward a kind of structural color filter with circular nanohole-nanodisk hybrid nanostructure arrays at sub-diffraction-limit spatial resolution based on the uncoupled localized surface plasmon polaritons (LSPPs). Due to the uncoupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The B* value of the CF 4 -RIE PET with a 75 nm pitch decreased from 0.61 to 0.50, while that of the Ar-RIE PET with a 35 nm pitch increased to 0.70. Zhao et al [34] and Purtov et al [35] revealed a correlation between the color and pitch of pillar array structures. Zhao et al [34] reported that the color of a silver/chromium/polymethyl methacrylate (PMMA) nanopillar structure with a 70 nm diameter and 150 nm height changed from brown to white (i.e., decreased in B*) with increasing the pitch.…”
Section: Resultsmentioning
confidence: 99%
“…The B* value of the CF 4 -RIE PET with a 75 nm pitch decreased from 0.61 to 0.50, while that of the Ar-RIE PET with a 35 nm pitch increased to 0.70. Zhao et al [34] and Purtov et al [35] revealed a correlation between the color and pitch of pillar array structures. Zhao et al [34] reported that the color of a silver/chromium/polymethyl methacrylate (PMMA) nanopillar structure with a 70 nm diameter and 150 nm height changed from brown to white (i.e., decreased in B*) with increasing the pitch.…”
Section: Resultsmentioning
confidence: 99%
“…Since the measurements were made using an FTIR microscope with a NA of 0.6, the incident angle is approximately 37° which may affect the spectral difference. In general, pillar type plasmonic nanodisc arrays are known to have superior angular tolerance compared with other metal nanohole arrays and guided-mode resonance filters that require momentum matching 26 , 27 . Nevertheless, in our simulation (now shown here), as the angle of incidence varies from 0° to 40°, the resonance wavelength redshifts just about 8% and the transmittance dip depth decreases by 17% for p-polarized light.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, spatial resolution of approximately 141,000 dpi with a wide gamut and large angle invariant was achieved by implementing circular nanohole-nano-disk hybrid nanostructure arrays based on the uncoupled Localized Surface Plasmon Polaritons (LSPPs) [ 171 ] ( Figure 5 c). The spanned across the visible regime by varying the diameter of the nanodisk-nanohole structure rather than its periodicity.…”
Section: Plasmonsmentioning
confidence: 99%
“…Copyright American Chemical Society, 2014. ( c ) Color printing resolution test pattern for LSPP based nanostructures at the scale bar of (i) 200 nm, (ii) 1 m and (iii) 500 nm [ 171 ].…”
Section: Figurementioning
confidence: 99%